A8.24 PPARβ/δ expression orchestrates the immunosuppressive effect of mesenchymal stem cells via NF-κB signalling. (13th February 2015) - Luz-Crawford, P; Ipseiz, N; Caicedo, A; Scholtysek, C; Stoll, C; Loriau, J; Tejedor, G; Jorgensen, C; Kronke, G; Djouad, F
Abstract : Introduction: PPARβ/δ is a member of the PPAR transcription factor family expressed by several cell types including mesenchymal stem cells (MSC). PPARβ/δ modulates signal transduction by interacting with other transcription factors such as NF-κB and regulates the expression of molecules such as VCAM-1 and ICAM-1. Lately, these adhesion molecules induced by proinflammatory cytokines were described to be critical for MSC immunosuppressive functions. Therefore, we investigated the role of PPRAβ/δ as an upstream regulator of MSC immunosuppressive properties. Materials and methods: MSC were isolated from the bone marrow of wildtype (MSC) and PPARβ/δ knockout mice (PPARβ/δ -/- MSC). The expression and production of immunosuppressive molecules by MSC were assessed after 24 h of culture in presence of proinflammatory cytokines by FACS analysis and ELISA, respectively. The role of NF-κB activity on adhesion molecule expression in MSC and T cell adhesion on MSC was addressed by FACS and under flow conditions, respectively. Chromatin immunoprecipitation (IP) assays were performed to study the interactions between transcription factors and co-repressors. Eventually, the therapeutic effect of PPARβ/δ -/- MSC was compared to the MSC in the collagen induced arthritis model (CIA). Results: In vitro, PPARβ/δ -/- MSC displayed a stronger immunosuppressive effect than MSC. This was associated with a higher production of NO, expression of V-CAM and I-CAM and NF-κB activity in PPARβ/δ -/- MSC compared to MSC. Conversely, the inhibition of NF-κB activity resulted in a loss of MSC immunosuppressive functions correlated with a significant decrease of adhesion molecule expression and NO production by MSC. Under flow conditions, while T cells attach to PPARβ/δ -/- MSC significantly more than wildtype MSC, the treatment with NF-κB inhibitor significantly impaired MSC attachment potential. Chromatin IP assays revealed that MSC activation with proinflammatory cytokines maintained NF-κB p65 subunit in the κB elements of the iNOS promoter. Under the same activation conditions, the knockdown of PPARβ/δ significantly increased the retention of NF-κB p65 subunit on iNOS promoter. In addition, we showed that pro-inflammatory treatment of MSC induces the release of the co-repressor CoREST in MSC while it is constitutively absent in PPARβ/δ -/- MSC. Finally, in vivo, in the CIA model we found out that PPARβ/δsilencingsignificantly increased the therapeutic effect of MSC. Conclusion: All together our results provide new insight into the mechanisms that mediate MSC immunosuppressive properties and highlight the role of PPARβ/δ as a potential means of enhancing MSC therapeutic potential in arthritis.